Lean Organization of Press tools At FBS Ltd. - SALAZAR, GIOVANNI (2007)
This dissertation describes 12 weeks internship at Fluorocarbon. The aims of this project are to improve the storage system and setup area in the press shop through application of 5S Which means that everything is displayed, marked, documented, and reported, so that any individual can be able to identify and allocate tooling and other parts needed to carry on production.